Digital Innovations in the Fiscal Policy of Ukraine: Promoting Sustainable Economic Development - Lukianykhina, Olena; Suprunenko, Svitlana; Slavkova, Alla; Skorba, Oleh; Zavrazhnyi, Kostiantyn (International Journal of Economics and Financial Issues, 2024)
This study critically examines the nexus between tax legislation and digital innovation in Ukraine, focusing on the alignment of fiscal policy with the digital economy’s growth. It analyzes the implications of Ukraine’s tax reforms, including the Law "On Stimulating the Development of the Digital Economy in Ukraine," commonly referred to as the Diia City initiative, for promoting a robust digital economy. This research evaluates the effectiveness of these reforms in fostering digital advancements and their impact on sustainable economic development. Employing a comprehensive multidisciplinary approach, it researches into the theoretical and practical aspects of tax policies, particularly those targeting the digital sector. The findings suggest Ukraine’s strategic positioning for leveraging digital innovation, underpinned by legislative reforms such as amendments to the Tax Code of Ukraine that cater to the IT industry through specific tax regulations through a conducive fiscal environment. This paper highlights the transformative potential of digital innovations and the critical need for tax legislation to evolve in tandem with technological advancements. Recommendations for ensuring the sustained success of Ukraine’s digital and economic reform efforts emphasize the importance of addressing existing obstacles and perpetually refining fiscal policies.